FINANCIAL EDUCATION AND LEVEL OF INDEBTEDNESS OF THE EMPLOYEES OF THE AUTONOMOUS UNIVERSITY OF ICA, 2018 - Meneses Jiménez, José Ángel (2019)
This article is based on a study carried out with the objective of determining the relationship between financial education and the level of indebtedness of the workers of the Autonomous University of Ica in the year 2018. Cross section with descriptive correlational design. The study population was made up of all the workers of the entity (n = 50) to whom a survey was applied for the recognition of data, consisting of 20 items. The results with respect to financial education that respondents almost always take into account the risks of financial credit prevention measures; In addition, at the same level of indebtedness, the study population has referred to the planning of their financial credits, although their income can not be reached. Finally, the Spearman correlation coefficient reaches a highly significant value for the statistical relationship between the variables financial education and level of indebtedness (r = .909). It is concluded that financial education determines the financial risks of the employees of the entity. It is recommended that the entity prioritize the development of workshops around financial education, and currently, in the future. KEYWORDS: Financial education; indebtedness; financial risk.